Kontrol Diri Dan Konformitas Teman Sebaya Dengan Perilaku Bullying Pada Siswi - Indri Kesuma Ningrum; Kamsih Astuti (Jurnal Psikologi, 2023)
ABSTRACT This study aims to determine: 1) the relationship between self-control and bullying behavior, 2) the relationship between peer conformity and bullying behavior, 3) the joint relationship between self-control and peer conformity and bullying behavior. The research sample was 142 high school students who had bullied. Methods of data collection in this study using the bullying scale, self-control scale and conformity scale. Data analysis using product moment correlation analysis and multiple linear regression. The results showed there was: 1) Negative relationship between self-control and bullying behavior, the correlation was -0.622 (p<0.01); 2) Positive relationship between conformity and bullying, correlation value is 0.626 (p<0.01); 3) The relationship between self-control and conformity with bullying obtained an F value of 73,592 and a correlation coefficient of 0.717 (p<0.01) and the effective contribution of self-control and conformity to predict bullying in students is 51.4% while the remaining 48.6% is influenced by other factors not examined in this study.